PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR FISIKA SISWA DI MTS DINIYAH PUTRI PEKANBARU - Silvia Dewi Lubis; Fakhruddin '; Zulirfan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aimed to describe and find out the improvement of the students motivation learning on physic by applying problem based learning model. This type of research is a quasi-experimental, with nonequivalent control group design. The subject of this research is students class VIII at MTs Diniyah Pekanbaru, total of 41 students as divide into two class, experimental class and control class. The data in this research is a score of motivation before and after learning physics by implementation of problem based learning and analysis of the data uses descriptive analysis. Then, measured the improvement of the students motivation by normalized gain (gain-N). The result of this research, score motivation of students at experimental class in high category and increase in the middle category with N-Gain 0,46, and the control class in the middle category with N-Gain 03. Therefore, it can be concluded that the implementation of problem based learning able to improve the motivation of students on physic at MTs Diniyah Putri Pekanbaru.Key Words: Learning Model, Problem Based Learning, Motivation..